"I Didn't Know People With Disabilities Could Grow Up to Be Adults": Disability History, Curriculum, and Identity in Special Education. (August 2021) - Mueller, Carlyn O.
The present qualitative interview study explored disability identity development, a unique aspect of identity, and its relationship to school and special education. Adults with disabilities ( n = 9) reflected on their schooling experiences in special education through a life history interview and semi-structured interview about their schooling experiences. The participants identified a lack of disability representation in curriculum, lack of connections to disability community, and lack of teachers and school community members as important factors to their sense of disconnection from disability identity and distancing themselves from their disability label during school. This study suggests the power and potential of special education to develop disability community and identity in students with disabilities. Implications for future research and practice are discussed.